(untitled) (Acta Entomológica Chilena, 2022)
The occurrence of the Eurytomid Systole albipennis Walker was detected in the Central Zone of Chile associaled to seeds of Petroselinum crispum (Mili.) Xym. (parsley), Daucus carota L. (wild carrot), Conium maculatum (cicuta) and Foeniculum vulgare Mili, (fennel). Damage percenlage fluctuates between 3.5 (parsley. wild carrol) and 5.5 (fennel).